You and Your Body - Raintree Steck-Vaughn; Nang ChanYeema (Austin, Texas USA Raintree Publishers Inc., 1986)
A reference book dealing with the workings of the human body, with special sections on the brain and senses, health, and reproduction
Keywords: Juvenile Nonfiction